Triplex-directed recognition of a DNA nanostructure assembled by crossover strand exchange. - Rusling, D; Nandhakumar, I; Brown, T; Fox, K (2012)
DNA has been widely exploited for the self-assembly of nanosized objects and arrays that offer the potential to act as scaffolds for the spatial positioning of molecular components with nanometer precision. Methods that allow the targeting of components to specific locations within these structures are therefore highly sought after. Here we report that the triplex approach to DNA recognition, which relies on the specific binding of an oligonucleotide within the major groove of double-helical DNA, can be exploited to recognize specific loci within a DNA double-crossover tile and array, a nanostructure assembled by crossover strand exchange. The oligonucleotide can be targeted to both crossover and non-crossover strands and, surprisingly, across the region spanning the crossover junction itself. Moreover, by attaching biotin to the end of the oligonucleotide, we show that streptavidin molecules can be recruited to precise locations within a DX array, with an average spacing of 31.9 (±1.3) nm. This is a promising approach that could be exploited to introduce other components compatible with oligonucleotide synthesis into the wide variety of DNA nanostructures assembled by crossover strand exchange, such as those generated by DNA origami.